(3JMaI GdCMHGH hHZjI GdWdGH aj GdNWW hGdeRGQGJs - (3fhQ GdOjf CHj GdMSf Ydj Hf CMeO Hf YeQ Hf Nda Hf eMehO GdSNGhj GdMfaj,J (B889 (3g` s
(3ChdgG (B:s
(3GdYHO GdQGLj Yah QHg jhe GdLRGA CHhGdMSf Ydi Hf CMeO GdSNGhi GdMfai HUQg Gddg HYjhH aSg hLYd jheg NjQkG ef CeSg s
(3BNQgG (B:s
(3hgh JMJ GdTHGc GdbHdj ef JQHI GHf YWGAGddg s
(3LGAJ fSHI GdcJGH aj agQS OGQ GdcJH GdeUQjI (B125/5 (3ddSNGhi GdeDQN eMeO Hf CHj HcQ Hf YKeGf GdeJhaj SfI (B902 (3g`s
(3hcPG LGAJ fSHI GdcJGH aj Pjd cTa GdXfhf (B238/1 (3hoeYLe GdeDdajf dcMGdI (B113/9s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B258s
Keywords: (3GdJGQjNs